The Importance of Timing in Optimizing Cranial Vault Remodeling in Syndromic Craniosynostosis. Issue 4 (April 2015) - Utria, Alan F.; Mundinger, Gerhard S.; Bellamy, Justin L.; Zhou, Joy; Ghasemzadeh, Ali; Yang, Robin; Jallo, George I.; Ahn, Edward S.; Dorafshar, Amir H.
Abstract : Background: The purpose of this study was to gain insight into the impact of age at repair on relapse rates in syndromic patients undergoing cranial vault remodeling. Methods: Retrospective chart review was performed for patients surgically treated for syndromic craniosynostosis from 1990 to 2013. Surgical procedures were assigned a Whitaker category based on need for reoperation as follows: no additional surgery required (category I); minor contouring revisions required (II); major revisions required (III); or failure of original surgery (IV). Age at surgery was grouped as follows: younger than 6 months; aged 6 to 9 months; and older than 9 months. Multivariable logistic regression analysis was performed to determine the relationship between age at surgery and need for reoperation by Whitaker category. Results: Fifty-two patients undergoing a total of 65 planned cranial vault remodeling procedures were included. Multivariate logistic regression analysis revealed that patients younger than 6 months at the time of primary surgery carried a 4.10 greater odds (95 percent CI, 1.31 to 12.87; p = 0.016) of requiring a subsequent major reoperation, and being older than 9 months of age carried a 13.2 greater odds (95 percent CI, 1.39 to 124.30; p = 0.024) of requiring a subsequent minor revision. Conclusions: Timing of surgery is an important factor to consider when planning vault remodeling in syndromic craniosynostosis. Based on our institution's experience, when there is no concern for elevated intracranial pressure the ideal operative window for these procedures in the syndromic population appears to be 6 to 9 months of age. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.